2013
DOI: 10.1186/1471-2164-14-426
|View full text |Cite
|
Sign up to set email alerts
|

Early transcriptional responses of internalization defective Brucella abortus mutants in professional phagocytes, RAW 264.7

Abstract: BackgroundBrucella abortus is an intracellular zoonotic pathogen which causes undulant fever, endocarditis, arthritis and osteomyelitis in human and abortion and infertility in cattle. This bacterium is able to invade and replicate in host macrophage instead of getting removed by this defense mechanism. Therefore, understanding the interaction between virulence of the bacteria and the host cell is important to control brucellosis. Previously, we generated internalization defective mutants and analyzed the enve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…Indeed, because erythritol is present in comparatively large amounts in the placenta and genital tissues of ruminants and swine and because Brucella is found inside trophoblastic cells of ruminants and uses erythritol very efficiently, it has been widely assumed that trophoblasts produce erythritol. However, most evidence is limited to extracts of fetal allantoic and amniotic fluids, cotyledons, whole placenta, seminal vesicles and testis (Smith et al, 1962; Williams et al, 1962; Clark et al, 1967), and to the best of our knowledge, only one work has reported the presence of erythritol in trophoblasts of bovine origin (Enright and Samartino, 1994). Our work confirms this pattern and provides the first experimental data that support the presence of erythritol in human and murine trophoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, because erythritol is present in comparatively large amounts in the placenta and genital tissues of ruminants and swine and because Brucella is found inside trophoblastic cells of ruminants and uses erythritol very efficiently, it has been widely assumed that trophoblasts produce erythritol. However, most evidence is limited to extracts of fetal allantoic and amniotic fluids, cotyledons, whole placenta, seminal vesicles and testis (Smith et al, 1962; Williams et al, 1962; Clark et al, 1967), and to the best of our knowledge, only one work has reported the presence of erythritol in trophoblasts of bovine origin (Enright and Samartino, 1994). Our work confirms this pattern and provides the first experimental data that support the presence of erythritol in human and murine trophoblastic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Present in substantial amounts in fetal fluids, placenta, seminal vesicles and semen of several ungulate species (Smith et al, 1962; Keppie et al, 1965; Clark et al, 1967), this four carbon polyol promotes Brucella growth at low concentrations and is also a preferred carbon source (McCullough and Beal, 1951; Smith et al, 1962). Bovine fetal tissues that were obtained from 6 to 7 months pregnant cattle (the time after which Brucella abortion often occurs) (Williams et al, 1962) and chorioallantoic membrane explants (Enright and Samartino, 1994) have been described to produce high amounts of erythritol. Nevertheless, other observations are not consistent with erythritol being the only factor in Brucella localization in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Brucella is known to prevent the activation of IFNγ or FasL-induced apoptosis both in infected and non-infected monocytes, suggesting the involvement of soluble factors 49 . Additionally, Brucella- infected cells are known to secrete TNFα 50 , 56 , 58 , 59 , 80 82 , a cytokine with a known dual effect. On the one hand, TNFα induces pro-survival NF-κB signalling and, on the other hand, in cases of excessive stimulation, it promotes apoptosis 83 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, characterization of the host macrophage- Brucella interaction is very important to identify the pathogenicity and infection mechanism of Brucella [ 22 ]. Microarray is a powerful approach that enables understanding the host responses at the global gene transcription level, thereby providing a plethora of information regarding the interactions associated with cell responses to antigens at the molecular level [ 15 , 23 ]. In this study, microarray analysis was used to compare the responses between macrophages infected with B. abortus wild-type and B. abortus mutant strains, to demonstrate the Brucella genes that affect the interactions between host immune cells and the bacteria.…”
Section: Discussionmentioning
confidence: 99%